Complementary And Alternative Use In Lung Cancer Patients Systematic Review - Ribka S Panjaitan; Yurita Mailintina; Ludovikus, Ludovikus; Kristoforus Marselinus; Nia Rosliany (Jurnal EduHealth, 2024)
Lung cancer is one of the deadliest cancers, with 2.21 million cases and 1.80 million deaths globally in 2020. In Indonesia, lung cancer is the third most common cancer with 34,783 cases in 2018. The five-year survival rate is very low, especially in advanced stages. Complementary and alternative medicine (CAM) is becoming increasingly popular among cancer patients as an adjunct to conventional therapy. This study aims to systematically review the impact of complementary and alternative therapies on lung cancer patients, evaluating the additional benefits of CAM in the treatment of lung cancer patients. This study employs a systematic review method, gathering data from scientific journals, clinical reports, and related publications, including PubMed, Science Direct, and SageJournal. The inclusion criteria were original research articles published in English between 2014 and 2024. Based on the search results, only 5 articles met the analysis criteria. The study shows that Chinese Herbal Medicine (CHM), Laughter Yoga, and Press Needling can improve the quality of life for lung cancer patients. CHM increases progression-free survival (PFS) and reduces chemotherapy side effects. Laughter Yoga reduces stress and enhances mental health. Press Needling decreases postoperative pain and pulmonary complications. Chinese Herbal Medicine (CHM) improves progression-free survival and overall survival (OS) for lung cancer patients, reduces chemotherapy side effects, and enhances quality of life without causing significant additional toxicity. CHM is widely accessible with insurance coverage, but interactions with modern medicine must be monitored.